Encyclopedia Americana on CD-ROM 1999 (Danburry, Conn. Grolier Educational, 1999)
Contains the complete text of the Encyclopedia Americana containing 45,000 articles written by 6,500 contributors; Merriam-Webster's Collegiate Dictionary, 10th ed., including definitions for over 150,000 terms; 1000 illustrations, plus glossaries; Helicon Publishing Company's Chronology of World History; Academic Press's Dictionary of Science and Technology containing over 130,000 entries in 125 fields of science and an on-screen tutorial
Keywords: Electronic encylopedias; Electronic reference sources; Electronic dictionaries; Science -- Dictionaries; Technology -- Dictionaries